Gamma-tocopherol vitamin E enhances the cytotoxicity of p-cresyl sulfate to renal tubular cells - Chyou-Wei Wei; Lin Jian; Shu-Cing Wu; Yi-Lin Chen; Ying-Ru Pan; Yi-Chung Chien; Jia-Yan Wu; Yung-Luen Yu; Giou-Teng Yiang (European Journal of Medical Research)
Abstract Background The protein-bound uremic toxins p-cresyl sulfate (PCS) and indoxyl sulfate (IS) are commonly found at elevated levels in patients with chronic kidney disease and can promote oxidative stress leading to the progression of renal disease. However, whether PCS or IS can directly cause renal-cell damage remains unknown. Vitamin E is comprised of eight major forms, one of which (gamma-tocopherol, γ-tocopherol) is commonly found in various cooking oils such as corn oil and soybean oil. Many studies have shown that γ-tocopherol has antioxidant effects although previous studies also indicated that it can induce cytotoxicity. The presence of γ-tocopherol in cooking oils raises the possibility that it may increase the cytotoxicity of protein-bound uremic toxins that can induce renal damage. Methods We studied the cytotoxic effects of different uremic toxins on renal cells and further investigated whether combinations of uremic toxins and γ-tocopherol had synergistic or antagonistic effects. Results Our result showed that γ-tocopherol is not cytotoxic to rat renal tubular epithelial NRK-52E cells, however, γ-tocopherol exerts cytotoxic effects on human renal tubular epithelial HK-2 cells through apoptotic death pathway. Moreover, γ-tocopherol can enhance the PCS-induced cytotoxic effects on NRK-52E and HK-2 cells. Conclusion In this study, our results constitute the first demonstration that γ-tocopherol may cause renal-cell damage and enhance PCS-induced toxicity to renal cells via the apoptotic cell-death pathway. Keywords: p-cresyl sulfate, indoxyl sulfate, gamma-tocopherol, renal tubular cells, synergistic effects.